2015
DOI: 10.1155/2015/365674
|View full text |Cite
|
Sign up to set email alerts
|

Biological Evidence Management for DNA Analysis in Cases of Sexual Assault

Abstract: Biological evidence with forensic interest may be found in several cases of assault, being particularly relevant if sexually related. Sexual assault cases are characterized by low rates of disclosure, reporting, prosecution, and conviction. Biological evidence is sometimes the only way to prove the occurrence of sexual contact and to identify the perpetrator. The major focus of this review is to propose practical approaches and guidelines to help health, forensic, and law enforcement professionals to deal with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 58 publications
0
53
0
10
Order By: Relevance
“…Saliva transports exfoliated epithelial cells from buccal mucosa which contains DNA and the mean number of epithelial cells per 1 mL of saliva is about 4.3 × 10 5 , which makes it a suitable source of genomic DNA (8,11,18). Some studies have shown that DNA of perpetrator may be detected in the victim's oral cavity up to 1 hour after intense or constrained kissing (8,10). Saliva can also be placed on human skin through kissing, biting, sucking and licking.…”
Section: Sources Of Dnamentioning
confidence: 99%
See 3 more Smart Citations
“…Saliva transports exfoliated epithelial cells from buccal mucosa which contains DNA and the mean number of epithelial cells per 1 mL of saliva is about 4.3 × 10 5 , which makes it a suitable source of genomic DNA (8,11,18). Some studies have shown that DNA of perpetrator may be detected in the victim's oral cavity up to 1 hour after intense or constrained kissing (8,10). Saliva can also be placed on human skin through kissing, biting, sucking and licking.…”
Section: Sources Of Dnamentioning
confidence: 99%
“…The fingernail hyponychium can provide a valuable source of evidential material for investigation (8,21). Traces of skin (especially if the victim scratched the perpetrator), body fluids and hairs may collect under the nails.…”
Section: Sources Of Dnamentioning
confidence: 99%
See 2 more Smart Citations
“…However, collecting biological samples beyond 72 hour after the occurrence greatly diminishes the chances of recovering the DNA profile from the perpetrator [4]. Sperm cells start lysing and the DNA becomes increasingly degraded, rendering an analysis impossible.…”
Section: Introductionmentioning
confidence: 99%